Configuring, optimizing and enhancing Dataverse: The case of SoDaNet Repositories - Linardis, Apostolos; Kondyli, Dimitra; Alexandris , Konstantinos; Papagiannopoulos , Konstantinos; Nisiotis , Konstantinos – Symeon; Mastoris , Nikolaos; Klironomos , Nicolas (The Greek Review of Social Research, 2024)
Current trends in computational social sciences and data-driven research require access to reliable data sources. Data repositories fulfil this role, providing high-quality data services, since they satisfy certain requirements that can be briefly summarized as complying with the FAIR data principles. In this context, we outline the measures undertaken by SoDaNet to enhance the data repositories within our infrastructure. Through the adoption and implementation of the Dataverse software, along with a series of adaptations and customizations, we have improved the Findability, Accessibility, Interoperability, and Reusability (FAIR) of the data hosted in these repositories. This effort has resulted in data repositories responding effectively to the demands of the research community, improving the user experience both nationally and internationally.